Relation between exercise, depression and body mass index - José Vasconcelos-Raposo; Helder Miguel Fernandes; Miriam Mano; Edith Martins (Desafio Singular, 2009)
The purpose of this study is to determine the relationship between physical exercise, depression, and body mass index (BMI). The sample of the study consisted of 175 participants (43 male and 132 female) with ages between the 18 and 27 years. The used instruments were: an adapted and validated Portuguese version of the Beck Depressive Inventory (BDI) and an adaptation of the physical exercise scale developed by Prochaska, Sallis and Long (2001). The results suggested a negative correlation between the physical exercise and depression, with statistical significance. The group that does not reach the recommended level of physical exercise presents higher scores of depression in comparison with the group that reaches. This study corroborates previous studies that suggested positive effects of physical exercise on depression.